PERAN DUKUNGAN LINGKUNGAN UNIVERSITAS DAN RELASI DALAM INTENSI BERWIRAUSAHA - Sienatra, Krismi; Firena Intan Anjani (STEKOM PRESS, 2020)
Entrepreneurship has not been career choice for freshgraduates in Indonesia. Entrepreneurial intention need to be increased to help solving the problem of unemployment in society and to increase the country's economic growth. The factors that influence entrepreneurial intention are university environment and support also relational support. University environment and support refers to the effort of university in increasing students’ entrepreneurial intention through educational support and cognitive support. Relational support refers to the approval and support from the family, friend, and people around to involve in entrepreneurial activity. This study aims to determine the influence of university environment and support and relational support to the entrepreneurial intention. The sampling technique that is used is accidental sampling, result the total sample of 204 peoples.. The result of multiple linear regression analysis shows that the the university environment and support and the relational support influence entrepreneurial intentions of students significantly